2016
DOI: 10.1038/srep37288
|View full text |Cite
|
Sign up to set email alerts
|

Plasma selenium levels and nonalcoholic fatty liver disease in Chinese adults: a cross-sectional analysis

Abstract: Selenium exposure can induce liver insulin resistance and increased liver triglyceride concentrations in animals, which may link to an increased risk of nonalcoholic fatty liver disease (NAFLD). However, epidemiological studies investigating the association between elevated plasma selenium levels and NAFLD were not available. We aimed to investigate the association of selenium levels with the prevalence of NAFLD in Chinese adults. This was a cross-sectional study of 8550 Chinese adults aged 40 yr or older in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 54 publications
(57 reference statements)
1
53
2
2
Order By: Relevance
“…The data presented in this article are based on the baseline survey of subsamples from Shanghai in eastern China [30, 31]. All studied individuals came from the Chongming District in Shanghai, China.…”
Section: Methodsmentioning
confidence: 99%
“…The data presented in this article are based on the baseline survey of subsamples from Shanghai in eastern China [30, 31]. All studied individuals came from the Chongming District in Shanghai, China.…”
Section: Methodsmentioning
confidence: 99%
“…The material presented in this study are based on the screen from Shanghai, China [17, 18]. Subjects who had complete material about sex; age; alcohol consumption habits and smoking; BMI, and a hepatic ultrasonic examination; and a medical history including the use of medications.…”
Section: Methodsmentioning
confidence: 99%
“…In 2016, a study on elderly individuals which was conducted in China ascertained that Se levels relate to type II diabetes due to increased glucose levels and their resistance to insulin [22]. Other Chinese scientists who carried out experimental studies during 2016 found out that increased Se levels relate with a more frequent presence of non-alcoholic fatty liver disease (NAFLD) and with increased triglyceride levels, LDL, fasting glucose, HBA1C, and insulin resistance [23].…”
Section: Discussionmentioning
confidence: 99%